(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
In this paper I am discussing the results of my research on the status and role of female coaches in Hungarian basketball. I researched the history of the international and Hungarian feminist movements with special focus on their effects on sports. I studied the beginnings of women’s appearance in sports and the widespread acceptance and expansion of women’s sports. My research is focused on female coaches in basketball in contemporary Hungarian society. I wanted to find out what percentage of the total number of Hungarian basketball coaches female coaches represent as well as their percentage in coaching the various age groups. I wanted to be able to answer questions about the professional results of female coaches and how their results are affected by their educational background and age. My research extended to questions about professional career/work and family life balance.